The Effect of Android-Based Digital Poster Learning Media on Students' Digital Literacy in Ecosystem - Suriyanto; Yusminah Hala; A. Mushawwir Taiyeb (Jurnal Penelitian Pendidikan IPA, 2025)
This research is motivated by the low digital literacy of biology of class X students of SMA Negeri 2 Luwu Timur. This study aims to determine the effect of android-based digital poster learning media on students' digital literacy in ecosystem material. This research is a quasi-experimental study with a Nonequivalent Control Group Design research design. The population of this study was all class X with a sample of 2 classes selected randomly. Which consists of 1 experimental class taught using android-based digital poster media, and 1 control class taught using wordwall-based open the box media. Data collection using a questionnaire given before and after treatment in the experimental class and control class. The results of the hypothesis testing at the digital literacy level showed a significance value of 0.023. This shows a sig value <α (0.05) so it can be concluded that H0 is rejected and H1 is accepted. This means that there is a difference in the influence of digital literacy of students taught using Android-based Digital Poster learning media and wordwall-based Open the Box learning media in class X Ecosystem material.